An investigation on recovery techniques for citric acid and acetic acid: A project study - De Leon, Hahnsen N. (Animo Repository, 1990)
Techniques of the recovery of citric acid and acetic acid from fermentation broth using conventional methods were investigated. Operations of two critical steps in citric acid recovery, liming and acidulation were optimized. It was found out that 25% lime at 50C gave the best result for a constant citric acid concentration in feed of 10.81 % W. For acidulation, 15% H2SO4 gave the maximum percent conversion of 94.74 %. For acetic acid recovery, a maximum of 50% W acetic acid was obtained after solvent extraction. The effect of azeotropic distillation was a further increase of concentration to at most 97% W acetic acid.